One and done? Outcomes from 3961 patients managed via a virtual fracture clinic pathway for paediatric fractures. (2021) - Kennedy, Jim; Blackburn, Carol; Barrett, Michael; O'Toole, Patrick; Moore, David
Abstract: Purpose: The aim of this paper is to describe our experience with a virtual fracture management pathway in the setting of a paediatric trauma service. Methods: All patients referred to the virtual fracture clinic service from the Paediatric Emergency Department (PED) were prospectively collected. Outcome data of interest (patients discharged, referred for urgent operative treatment, referred back to emergency department for further evaluation, referred for face-to-face clinical assessment and all patients who re-presented on an unplanned basis for further management of the index injury) were compiled and collated. Cost analysis was performed using established costing for a virtual fracture clinic within the Irish Healthcare System. Results: There were a total of 3961 patients referred to the virtual fracture clinic from the PED. Of these, 70% (n = 2776) were discharged. In all, 26% (n = 1033) were referred to a face-to-face appointment. Of discharged patients, 7.5% (n = 207) required an unplanned face-to-face evaluation. A total of 0.1% (n = 3) subsequently required operative treatment relating to their index injury. Implementation of the virtual fracture clinic model generated calculated savings of €254 120. Conclusion: This prospective evaluation has demonstrated that a virtual fracture clinic pathway for minor paediatric trauma is safe, effective and brings significant cost savings. Level of Evidence: II